CELL SIZE OF DIFFERENTS TRAYS ON SEEDLINGS PRODUCTION AND PAK CHOI YIELD WITH OR WITHOUT NONWOVEN POLYPROPYLENE - REGHIN, Marie Yamamoto; OTTO, Rosana Fernandes; van der VINNE, Jhony (Scientia Agraria, 2003)
The experiment was carried through in Ponta Grossa (PR) and had the aim to avaluate pak choi seedlings production on trays of 72, 128, 200 and 288 cells and its effects on plants yield, with or without nonwoven of polypropylene of 25 g. m-2. The experimental design was a randomised blocks with four replications; the treatments followed a factorial scheme 4 x 2. Seeds of Fuyuhasen hybrid were sowed in 03/08/2003 under protected cultivation on trays with the substrate Plantmax®. Before transplanting the seedlings were avaluated at the characteristics of leaves number, lenght of upper part and root, fresh and dry weight of up ground material and root. The seedlings were transplanted on plots having four rows arranged in 0,25 x 0,25 m. Thereafter nonwoven of polypropylene was stretched out on the plants. The plants were harvested in according on its maturity. On the seedlings stage it was observed the cells volume on differents trays had important infuence on seedlings development. As bigger was the cell volume more expressive was the development. The data obtained at harvesting did not show significative effect of interaction. Seedling type and crop system showed isolate effect. Seedlings from trays of 72 cells also presented influence at the crop development and promoted early harvest of six days when compared to trays of 288 cells. Nevertheless each one of the seedlings from trays of 128, 200 and 288 cells produced plants of commercial size. The choice of seedling type depends on how big it is expected to yield the plant and which one is the market. Plants under polypropylene showed lower yield when compared to plants without it. With polypropylene the decreasing of solar radiation limited the photosynthesis of the hybrid Fuyuhasen.